Seed-mediated growth of Ag nanocubes and their size-dependent activities toward oxygen reduction reaction. (19th February 2016) - Chao, Yi-Ju; Lyu, Yuan-Ping; Wu, Zheng-Wei; Lee, Chien-Liang
Abstract: A non-epitaxial growth method for the synthesis of Ag nanocubes by using Pt seed crystals was successfully developed. Tuning the amount of Pt seeds introduced into the reaction allowed for precise control over the size of the Ag nanocubes from 12 nm to 38 nm. Further experiments demonstrated the size-dependent properties of surface oxides and specific activities in terms of electrochemical surface areas for these Ag nanocubes to act as oxygen reduction catalysts in the KOH solution without and with methanol. Graphical abstract: Highlights: Ag nanocubes enclosed (100) planes are successfully synthesized using Pt seeds. Sizes of Ag nanocubes are controlled by different amounts of Pt seed solution. Ag nanocubes show their potential as electrocatalysts in oxygen reduction. Size-dependent specific activities of Ag nanocubes are observed.